Applying Personality Traits to Predict Loyalty and Neglect among Employees of Bank Jatim Located in 10 Big Cities of East Java (Mc Crae’s and Hofstede’s Theories on effect of Culture to Personality Revisited) - Rajiani, Izmi (Universitas Brawijaya, Indonesia, 2010)
This study links the relationship of culture and personality on how employees behaves in organizations . The workplace behaviors are displayed in the form of Loyalty or Neglect .The hypotheses are tested through sample of 253 employees of local Javanese bank located in 10 big cities of East Java and structural equation modeling is used. Applying Hogan Personality Inventory (HPI) , The Big Five Factor personality in this research is labeled as Adjustment (Emotional Stability), Sociability (Extraversion), Likeability (Agreeableness), Prudence (Conscientiousness) and School success (Openness to Experience) . Since Sociability (Extraversion), is positively related with Individualism while Indonesian is scored low on this dimension , this variable is excluded from the model. Besides proving the existence of the sixth trait labeled by Hofstede as Dependence on Others trait among Javanese Indonesian, the research also found the trait of Likeability (Agreeableness) which is the typical of Javanese in where they attempt at all times to maintain harmony. The finding reveals that loyalty is better predicted by dependence on others mediated through normative commitment.